TEACHER’S SPEECH AS A COMMUNICATIVE TOOL (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Teacher's speech plays a vital role as a communicative tool in the classroom, significantly influencing the effectiveness of the teaching-learning process. It encompasses both verbal and non-verbal elements such as tone, intonation, clarity, body language, and pacing, which help in delivering content, managing the classroom, and engaging students. A teacher’s language choice, questioning strategies, and feedback methods are instrumental in fostering a supportive and interactive learning environment. Moreover, teacher talk aids in scaffolding students' cognitive and linguistic development, particularly in language learning settings. This paper explores the communicative functions of teacher speech, analyzing its impact on student participation, motivation, and comprehension. Emphasis is placed on the need for conscious and reflective use of speech by educators to optimize classroom communication and promote effective learning.